2021
DOI: 10.1007/s00296-021-05003-1
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitative management of post-acute COVID-19: clinical pictures and outcomes

Abstract: This study aimed to detect patients' characteristics who suffered severe and critical COVID-19 pneumonia admitted to the post-acute COVID-19 rehabilitation clinic in Ankara City Hospital, Physical Medicine and Rehabilitation Hospital and to share our experiences and outcomes of rehabilitation programmes applied. This study was designed as a single-centre, retrospective, observational study. Severe and critical COVID-19 patients, admitted to the post-acute COVID-19 rehabilitation clinic, were included in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 29 publications
0
39
0
1
Order By: Relevance
“…Among the 159 full-text articles assessed for eligibility, 124 were removed for different reasons further detailed in Figure 1 . Finally, 35 studies [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ] remained at the end of the study selection. As detailed in Figure 2 , the global score for the risks of bias in-between studies were found to be heterogeneous, ranging from 31% [ 65 ] to 88% [ 40 , 47 , 57 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the 159 full-text articles assessed for eligibility, 124 were removed for different reasons further detailed in Figure 1 . Finally, 35 studies [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ] remained at the end of the study selection. As detailed in Figure 2 , the global score for the risks of bias in-between studies were found to be heterogeneous, ranging from 31% [ 65 ] to 88% [ 40 , 47 , 57 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 35 studies [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ] remained at the end of the study selection. As detailed in Figure 2 , the global score for the risks of bias in-between studies were found to be heterogeneous, ranging from 31% [ 65 ] to 88% [ 40 , 47 , 57 , 68 ]. The higher risk of bias was observed for the ‘blinding of participants/personnel’ parameter assessed as ‘moderate risk’ for 94% [ 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations